Online Discussion Strategies to Facilitate Undergraduate Students’ Discussion in a Technical University - Omar, Azura; Amir, Zaini; Mohamad, Maslawati (International Journal of Engineering and Technology, 2018)
The use of online discussion forum is slowly integrated into classroom teaching and learning as studies have proven that it contributes to positive learning environment. In order to know how to use the online discussion forum effectively, this study was conducted. The research objective was to identify the online discussion strategies employed by the participants.  This case study involved fifteen second semester Engineering Technology Malaysian undergraduates. Data were gathered from a focus group interview, individual interview and participants’ reflective notes. Five participants volunteered to be interviewed individually and the remainder were interviewed in a focus group interview. The participants were interviewed immediately after their online discussion activities. The participants were also asked to reflect on their opinions regarding their online discussion experience after each online discussion activities. These findings indicate that participants employed three online discussion strategies to facilitate their project work, namely: 1) outlining and organising ideas before posting 2) understanding others’ responses before posting their ideas online, and 3) reconfirming their own statements before posting.